The Risk of QTc Prolongation in Non-Diabetic and Diabetic Patients Taking Tyrosine Kinase Inhibitors (TKIs)- A Patient Safety Project at a Private Oncology Practice - Zhongju Lu (Taylor & Francis Group, 2021)
Objective: To assess the prevalence of QTc prolongation in both non-diabetic and diabetic patients on TKIs. Some TKIs have been reported to cause QTc prolongation, which is prevalent in diabetes. However, there is no Risk Evaluation and Mitigation Strategy using series ECG to monitor those patients. Methods: Patients taking TKIs, with two ECGs recorded between 1 January 2010 and 31 December 2017 were selected from the electronic database. The QTc duration >450 ms was determined as prolonged. Percentage of QTc prolongation on participants were compared using Chi-Square test. Results: This study included 313 patients (age 66.1 ± 0.8 years and 57.5% are female) taking TKIs. In non-Diabetic patients, the prevalence of QTc prolongation is 19.1% (n = 253) before and 34.8% (n = 253) after treatment with TKIs (p < 0.001), respectively. In diabetic patients, the prevalence of QTc prolongation is 21.7% (n = 60) before and 40% (n = 60) after treatment with TKIs (p = 0.03), respectively. In addition, we examined the effect of modifying risk factors for cardiovascular disease (CVD) on the prevalence of QTc prolongation caused by TKIs. In non-diabetic patients, the prevalence of QTc prolongation is 33.3% (n = 57) before and 34.2% (n = 196) after risk factors modification (p = 0.91), respectively. In diabetic patients, the prevalence of QTc prolongation is 50% (n = 24) before and 33.3% (n = 36) after risk factors modification (p = 0.20), respectively. Conclusion: Use of TKIs is associated with a significantly increased risk of QTc prolongation for patients, particularly when patients are diabetic. Modification of risk factors for CVD does not significantly affect the prevalence of QTc prolongation caused by TKIs.